LITERATURE AND SOCIETY: THE AFRICAN LITERARY MACROSYSTEM (International Seven Journal of Multidisciplinary, 2025)
How is the contemporary African literary macrosystem composed? In light of this research question, this paper aims to explain the concept of literary system and its limitations in its application to African countries. Using the comparative literature method, 25 fictional works from Angola, Mozambique, Nigeria, Kenya, Algeria, Rwanda and South Africa are approached as a corpus for investigative analysis. The argumentation cores indicate that a) conceiving African literature from the conceptual perspective of macrosystem seems more appropriate to us than independent national literary systems, even if this may hinder the understanding of the process of national identity construction; b) postcolonial literature feeds back into this artistic macrosystem, to the extent that the decolonial strategy is configured as the main modernist discursive mechanism of the African novel throughout the 20th and 21st centuries; c) sharing the same European language for disseminating the African novel seems to be insufficient to think about literary systems and macrosystems.